The noise [large type] - Patterson, James, 1947-; Barker, J. D. (Jonathan Dylan), 1971- (Little, Brown and Company, 2021)
"In the shadow of Mount Hood, sixteen-year-old Tennant is checking rabbit traps with her eight-year-old sister Sophie when the girls are suddenly overcome by a strange vibration rising out of the forest, building in intensity until it sounds like a deafening crescendo of screams. From out of nowhere, their father sweeps them up and drops them through a trapdoor into a storm cellar. But the sound only gets worse..."--